Analisis Citraan dalam Novel Badboy-ku Imamku Karya Hann Lestari - Sri Rahayu; Alintang Raya Milaniza; Delvi Witri Haryani; Haura Hafizhah; Meitia Haspita Rani; Olivia Olivia; Siti Aisyah; Zilfa Zaldiah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study discusses the analysis of imagery in the novel Badboy-ku Imamku by Hann Lestari. The purpose of this study is to describe the use of various types of imagery found in the novel, namely auditory, olfactory, tactile, motion, and visual imagery. The method used is descriptive qualitative with data collection techniques in the form of reading techniques and note-taking techniques. The research data are in the form of quotations in the novel that contain elements of imagery. The results of the study show that all types of imagery are found in the novel, with the most common imagery being visual imagery, tactile imagery, and motion imagery. The use of these imagery is able to strengthen the description of the atmosphere, the emotions of the characters, and the course of the story so that it is more vivid and easily understood by the reader.